IMPLEMENTATION OF PANCASILA AND CITIZENSHIP EDUCATION TO INCREASE DEMOCRATIC AWARENESS OF MADRASAH IBTIDAIYAH TEACHER EDUCATION (PGMI) STUDENTS IN COLLEGE - Alifia khairullina; Mohamad Agung Rokhimawan; Sukati (El Midad, 2025)
This study aims to analyze the implementation of Pancasila and Citizenship Education in increasing the democratic awareness of undergraduate Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program students at Alma Ata University Yogyakarta. This research uses a descriptive quantitative approach, with data collection techniques through questionnaires distributed online using Google Form to students who have taken Civic Education courses. The data obtained were analyzed using the SPSS program with the Analyze Descriptive Statistics Frequencies technique, focusing on variable S which represents the level of student democratic awareness. The results of the analysis showed a high frequency in the indicators of understanding democratic values, active participation in campus organizations, and a tolerant attitude towards differences, which indicated that learning Civic Education made a positive contribution to increasing students' democratic awareness. This finding indicates the importance of strengthening contextualized learning materials and strategies to shape the character of democratic citizens in higher education.